Tough and conductive polymer hydrogel based on double network for photo-curing 3D printing - Xueyuan Ding; Runping Jia; Zuzhong Gan; Yong Du; Dayang Wang; Xiaowei Xu (Materials Research Express, 2020)
Conductive hydrogels (CHs) have attracted significant attention in wearable equipment and soft sensors due to their high flexibility and conductivity. However, CHs with high-strength and free-structure still need to be further explored. Herein, 3D printing high-strength conductive polymer hydrogels (CPHs) based on a double network was prepared. Firstly, PHEA-PSS hydrogels were prepared by copolymerizing 2-Hydroxyethyl acrylate (HEA) with 4-Vinylbenzenesulfonic acid (SSS) using a photo-curing 3D printer. Then 3, 4-Ethylenedioxythiophene (EDOT) was in situ polymerized in the network of PHEA-PSS to obtain the PHEA-PSS/PEDOT hydrogels. It can not only satisfy the printing of complex spatial structures, but also has high mechanical and electrical properties. When the content of EDOT is 12 wt%, the tensile strength of the PHEA-PSS/PEDOT hydrogels is close to 8 MPa, the electrical conductivity reach to 1.2 S cm ^−1 and the elasticity remain unchanged. Due to the presence of hydrogen and coordination bonds, CPHs have certain self-heal ability. In addition, the resistance of the hydrogel is sensitive to the changes of external pressure. The results show that CPHs can be used as a 3D printing material for flexible sensors.